Pengaruh Citra Merek, Promosi dan Harga Terhadap Keputusan Pembelian Produk Air Minum dalam Kemasan (AMDK) Merek Club di Kota Bandung - Fuadah, Asri Tsamrotul; Akbar, Ridho Riadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine how brand image, promotion, and price influence purchasing decisions on Club brand bottled drinking water in Bandung City. Quantitative methods were used in this study, which used descriptive and verification approaches with primary and secondary data. Researchers involved 100 people selected using the Slovin formula from 2,469,589 people. This study shows that elements such as Price, Promotion, and Brand Image have a significant influence on purchasing decisions for Club brand bottled water. According to the data, Brand Image has a significant influence with a tcount value of 2.182 and a significance level of 0.032. Meanwhile, Promotion does not have a significant influence with a tcount value of 1,650 and a significance level of 0.032. In addition, price also has no significant effect on purchasing decisions, as indicated by the t value of 1.137 with a significance level of 0.258. On the other hand, the calculated f value of 9.668 and a highly significant pvalue of 0.000 indicate that these three factors have a significant influence on purchasing decisions.